Clinico-Epidemiological Study of Intraarticular Phalangeal Fractures in Eastern Nepal - Khanal, Guru Prasad; Rijal, R; Shrestha, B P; Chaudhary, P; Maharjan, R; Paneru, S R; Kalawar, RPS (Health Renaissance, 2015)
Background: Fractures and dislocations of the hand are the most common injuries seen in emergency departments. Intraarticular fractures have worst functional outcomes if not managed properly. Objective: To find out the incidence and pattern of intra articular phalangeal fractures in the eastern part of Nepal Methods: Patients presenting at Emergency department of B.P.Koirala institute of Health Sciences between 1st January 2009 and 31st December 2009 and who were diagnosed as phalangeal fractures of hand were included in the study. These patients were reviewed for age at time of injury, gender, location of the incident, mechanism of injury, site of injury, side, hand dominance and mode of treatment. Results: One hundred and one patients were included in the study after excluding twenty patients with other associated injuries like head injury (6), poly trauma (10) or those not giving consent (4). The age ranged from 3 to 76 years. Among them male were 79.2%. Farm related injuries were the most common cause in both the sexes. Left side was the most involved side. Most of the patients attended hospital more than 4 hours after injury. Among them 74% had open fracture. Proximal phalanx was involved in 54.4% of cases. Pattern of involvement was mostly oblique and transverse. Most of the patients were undergone wound debridement and Kirschner wire fixation. Conclusion: Farm related and household events are commonest causes of hand injuries with intraarticular phalangeal fractures in our set up. Young males belonging to economically productive age group are mostly affected by these fractures. DOI: http://dx.doi.org/10.3126/hren.v12i1.11982 Health Renaissance 2014;12(1):29-32